Efficacy and safety of checkpoint inhibitor treatment in patients with advanced renal or urothelial cell carcinoma and concomitant chronic kidney disease: a retrospective cohort study - Seydel, Florian; Delecluse, Susanne; Zeier, Martin; Holland-Letz, Tim; Haag, Georg Martin; Berger, Anne Katrin; Grün, Barbara; Bougatf, Nina; Hohenfellner, Markus; Duensing, Stefan; Jäger, Dirk; Zschäbitz, Stefanie (Cancers, 2021)
Background: Checkpoint inhibitors are a standard of care in the treatment of advanced renal cell carcinoma (RCC) and urothelial carcinoma (UC). Patients with these tumors often suffer from concomitant chronic kidney disease (CKD). Limited data are available on the efficacy and toxicity of checkpoint inhibitors in patients with CKD. Methods: We retrospectively analyzed 126 patients who received checkpoint inhibitors for RCC (n = 85) or UC (n = 41) and analyzed the frequency of treatment- and immune-related adverse events (AEs). We performed a multivariate analysis to determine progression-free survival (PFS) and overall survival (OS). Results: A total of 38.9% of patients had CKD. Frequencies of general AEs (49.0% in CKD vs. 48.1%, p > 0.99999) and immune-related AEs (28.6 vs. 24.7%, p ≥ 0.9999) did not significantly differ between the groups. There was no difference in PFS for patients with RCC or UC and CKD or without CKD (RCC: 6.81 vs. 7.54 months, HR 1.000 (95%CI 0.548-01.822), p = 0.999; UC:2.33 vs. 3.67 months, HR 01.492 (95%CI 0.686-3.247), p = 0.431). CKD appeared to be a potential effect modifier for OS in both RCC and UC (RCC: NR vs. 23.9 months, HR 0.502 (95%CI 0.219-1.152), p = 0.104; UC:18.84 vs. 15.42 months, HR 0.656 (95%CI 0.296-1.454), p = 0.299). Conclusions: Checkpoint inhibitor treatment in our cohort of patients with CKD was as safe and efficient as in the cohort of patients without CKD.